Creativity, Automaticity, Irrationality, Fortuity, Fantasy, and Other Contingencies: An Eightfold Response Typology. Issue 2 (June 2016) - Simonton, Dean Keith
A 4-decade long research program that had started out focusing on creative genius unexpectedly produced a general response typology potentially applicable to the average person on the street. In particular, attempts to define both creativity and noncreativity resulted in an eightfold typology of everyday human thought and behavior. Given any situation that may evoke a response, the alternative outcomes can be distinguished according to their initial probability, actual utility, and the person's prior knowledge of that utility. These 3 parameters then yield 8 major types of outcomes: (a) routine, reproductive, or habitual responses (based on acquired life and work expertise); (b) fortuitous responses (such as uninformed response biases); (c) irrational perseveration (or failing to learn from past mistakes); (d) problem finding (such as violations of expert expectations); (e) irrational suppression (refusing to do what's good for you); (f) creative or productive thoughts and behaviors (original, useful, and surprising responses); (g) rational suppression (such as those due to previous response extinction); and (h) mind wandering and behavioral exploration (such as fantasy, tinkering, and play). These distinct responses exhibit important interrelationships. For example, although habitual responses are antithetical to creative thought and behavior, creativity is fostered by problem finding, rational suppression, and mind wandering or behavioral exploration. Moreover, because the 3 parameters can assume continuous values between 0 and 1 inclusively, the typology allows for more finely differentiated thoughts and behaviors, including "satisficing" decisions that fall short of utility optimization as well as tentative hunches residing between absolute ignorance and certain knowledge.